2003
DOI: 10.1046/j.1471-4159.2003.01987.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated 5‐HT1A receptor signaling in brains of suicide victims: involvement of adenylyl cyclase, phosphatidylinositol 3‐kinase, Akt and mitogen‐activated protein kinase

Abstract: Positron emission tomography studies in major depression show reduced serotonin (5-HT) 1A receptor antagonist-binding potentials in many brain regions including occipital cortex. The functional meaning of this observation in terms of signal transduction is unknown. We used postmortem brain samples from depressed suicide victims to examine the downstream effectors of 5-HT 1A receptor activation. The diagnosis was established by means of psychological autopsy using Diagnostic and Statistical Manual of Mental Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
0
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 58 publications
8
100
0
5
Order By: Relevance
“…Interestingly, we found abnormalities in ERK-1/2 signaling in postmortem brain of these subjects, such that expression and activation of ERK-1/2 are decreased and expression of MAPK phosphatase1, involved in dephosphorylation and deactivation of ERK1/2, is increased (Dwivedi et al, 2001). Similar attenuation of ERK-1/2 activation has also been reported in postmortem brain of suicide subjects by Hsiung et al (2003). In addition, very recently, we reported that in ERK signaling, the upstream kinase B-Raf is less activated in postmortem brain of these subjects (Dwivedi et al, 2006).…”
Section: Introductionsupporting
confidence: 83%
“…Interestingly, we found abnormalities in ERK-1/2 signaling in postmortem brain of these subjects, such that expression and activation of ERK-1/2 are decreased and expression of MAPK phosphatase1, involved in dephosphorylation and deactivation of ERK1/2, is increased (Dwivedi et al, 2001). Similar attenuation of ERK-1/2 activation has also been reported in postmortem brain of suicide subjects by Hsiung et al (2003). In addition, very recently, we reported that in ERK signaling, the upstream kinase B-Raf is less activated in postmortem brain of these subjects (Dwivedi et al, 2006).…”
Section: Introductionsupporting
confidence: 83%
“…Recently it was reported that PI 3-kinase activity is decreased in occipital cortex of suicide subjects (Hsiung et al, 2003) and that ECS (Altar et al, 2004) or long-term lithium treatment (Chalecka-Franaszek and Chuang, 1999) increases PI 3-kinase activity. Given the role of PI 3-kinase in a plethora of biological functions, these and our present findings appear to be quite significant and suggest the possibility that dysfunction of PI 3-kinase signaling may be important in the pathophysiologic mechanisms of suicide.…”
Section: Discussionmentioning
confidence: 99%
“…PI 3-Kinase Activity Assay P13-K activity was measured essentially by the procedure described by Hsiung et al (2003). Postmortem brain lysates (600 mg protein) were immunoprecipitated with an antibody directed against the p85 subunit and incubated on ice for 60 min.…”
Section: Preparation Of Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that impaired receptor sensitivity (Cowen et al, 1994) or altered signaling (Lesch et al, 1990) could account for the apparent decreases in receptor abundance, although post-transcriptional regulation and protein degradation (Young et al, 1987;Busquets et al, 1997;Ventayol et al, 1997) could also be involved in the differences observed between receptor mRNA and protein levels. In fact, a functional impairment of 5-HT 1A -associated signaling is originated by alteration of downstream transduction proteins in the brains of suicides (Hsiung et al, 2003). Moreover, a lower serotonergic activity associated with suicidal behavior has been also shown through positron emission tomography studies in depressed subjects and radioligand binding studies in post-mortem brain of suicides (Oquendo et al, 2003;Stockmeier et al, 1998).…”
Section: Altered 5-ht Receptor Expression In the Brains Of Suicide VImentioning
confidence: 99%